notes13

# notes13 - 5.73 Lecture #13 1. 13 - 1 End Matrix Solution of...

This preview shows pages 1–4. Sign up to view the full content.

13 - 1 5.73 Lecture #13 updated 9/27/02 9:22 AM End Matrix Solution of H-O, a + a Operators 1. starting from H = p 2 2 m + 1 2 k x 2 and [ x , p ] = i h 2. showed p nm = m i h x nm E m E n () x nm = i h k p nm E m E n x nn =0 ,p nn and x nm p nm if E n = E m 3. x nm 2 =− 1 km p nm 2 E m E n i h ωω = km 1/2 the only non-zero x and p elements are between states whose E’s differ by ± h ω 4. combs of connected states, block diag. of H , x , p , x 2 , p 2 E n (i) = h ω n i 6. Recursion Relationship 5. lowest index must exist because lowest E must exist. Call this index 0 x 01 2 = h 2 (km) p 01 2 = h 2 + from phase choice x 01 =+ i p 01 Today x nn + 1 2 in terms of x nn-1 2 general matrix elements x nn + 1 2 nn + 1 2 7. general x and p elements 8. only blocks correspond to ε i = 1 2 h ω Dimensionless x, p, H and a (annihilation) and a (creation) operators

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
13 - 2 5.73 Lecture #13 updated 9/27/02 9:22 AM phase ambiguity: we can specify absolute phase of x or p BUT NOT BOTH because that would affect value of [ x , p ] matrix elements of x are REAL p are IMAGINARY BY CONVENTION: x 01 =+ i km () −1 / 2 p 01 and plug this into x 01 p 01 * p 01 x 01 * = i h try x 01 2 = h 2 km 1/2 p 01 2 = h 2 km + get If we had chosen we would have obtained x which is impossible! 01 xk m p km 01 12 01 2 2 =− i / / h check for self-consistency of seemingly arbitrary phase choices at every opportunity: * Hermiticity * 2 0 Recursion Relation for x ii + 1 2 6. start again with gerand equation derived in #3 above using the phase choice that worked above x n + 1n * = i km p n + 1n * going up Hermiticity c.c. of both sides x nn +1 = i(km) −1 / 2 p nn going down x i km p nn + + 1 1 /
13 - 3 5.73 Lecture #13 updated 9/27/02 9:22 AM x nn ± 1 i km () 1/2 p nn ± 1 now the arbitrary part of the phase ambiguity in the relationship between x and p is eliminated Apply this to the general term in [ x,p ] algebra NONLECTURE : from terms in [ x , p ] = i h x nn + 1 p n + 1n = x nn + 1 p nn + 1 * = x nn + 1 km i x nn + 1 * = x nn + 1 2 + i km p nn + 1 x n + 1n =− km i x nn + 1 x nn + 1 * = x nn + 1 2 + i km x nn 1 p n 1n = x nn 1 p nn 1 * = x nn 1 + km i x nn 1 * = x nn 1 2 i km p nn 1 x n 1n =− − km i x nn 1 x nn 1 * = x nn 1 2 i km i h = 2 i km x nn + 1 2 x nn 1 2 [] x nn + 1 2 = h (km) 2 + x nn 1 2 but x 01 2 = x 10 2 = h 2 km x nn + 1 2 = n + 1 h 2 km p nn + 1 2 = n + 1

This preview has intentionally blurred sections. Sign up to view the full version.

View Full Document
This is the end of the preview. Sign up to access the rest of the document.

## notes13 - 5.73 Lecture #13 1. 13 - 1 End Matrix Solution of...

This preview shows document pages 1 - 4. Sign up to view the full document.

View Full Document
Ask a homework question - tutors are online